The Effect of Health Promotion on Prevention of Covid-19 Transmission Using Audio Visual Media on Changes in People's Behavior - Edy Siswantoro; Sutomo Sutomo (Universitas Islam Lamongan, 2021)
Covid-19 is a disease caused by the corona virus that has become a pandemic throughout the country. Adhering to health protocols by implementing 6M has proven to be one of the efforts to prevent the transmission of Covid-19. This study aims to determine the effect of health promotion on preventing the transmission of covid-19 using audio-visual media on changes in people's behavior. The research design used is a pre-experiment with a One-Group Pre-Post Test Design approach. The sample in this study were 40 respondents who were determined by simple random sampling technique. The research instrument used was a closed questionnaire sheet. After the data was collected, it was analyzed using the Wilcoxon Signed Rank Test for the Pre-Post Test. The results showed that there was an effect of health promotion on preventing the transmission of covid-19 using audio-visual media on changes in people's behavior with a significance value of 0.002 < (0.05). Prevention of Covid-19 by implementing 6M can be a good way to always use a mask when doing activities outside the home, washing hands with soap and running water or using hand sanitizer regularly, avoiding touching the face area when outside the house, avoiding oneself from crowds, reduce mobility and maintain distance from other people. Compliance with the implementation of the 6M health protocol will help the program to break the chain of transmission and spread of COVID-19 in Indonesia